Prevention of biliary complications after extensive liver resections: Single-center experience - M. A. Nartailakov; F. R. Nagaev; D. M. Minigalin; M. R. Bakeev; A. G. Safargalina (Креативная хирургия и онкология)
Introduction. Biliary complications are serious and life-threatening complications after major liver resections. Prevention of these conditions is important for successful treatment. Aim. This study aims to evaluate the method for intraoperative drainage of the extrahepatic biliary tract as a way to prevent post-resection biliary complications.Materials and methods. The results of surgical treatment of patients with liver diseases for the period of 2020–2024 were analyzed; patients were given treatment in the surgical department of the BSMU Clinic. The results of 61 patients who underwent extensive liver resections are presented. The experimental group included 31 (50.8%) patients who underwent intraoperative biliary drainage, and the control group included 30 (49.2%) patients who had no drainage. Perioperative criteria were compared between the two groups. Statistical data processing was performed using Statistica 10.0 program; the level of statistical significance was analyzed at p < 0.05.Results. Statistically significant differences were observed between the groups in terms of operative intervention time and duration of hospitalization. In the experimental group, surgical interventions lasted longer (p < 0.05), while the duration of hospitalization was shorter (p < 0.05). At the same time, no differences were found in terms of intraoperative blood loss, volume of blood transfusions, and time to restore normal intestinal function (p > 0.05). According to statistics, the level of total bilirubin was significantly lower in the experimental group on the third day after surgery (p < 0.05). The control group demonstrated a total of more post-resection biliary complications compared with the experimental group (7 (23.3%) and 3 (9.7%), respectively, p < 0.05). Discussion. The data from world literature sources demonstrate the advantages of intraoperative biliary drainage. Prognostic scales are being developed to predict biliary complications.Conclusion. The presented method significantly reduces the risk of biliary complications after extensive liver resections.